A Fast and High-Resolution Multi-Target Localization Approach in MIMO Radar. (9th September 2013) - Zhang, Yu; Jiang, Hong; Wei, Ying-Chun; Cui, Hai-Jing
This paper presents a fast and high-resolution estimation approach using polarization information combined with angle information for multi-target localization in bistatic multiple-input multiple-output (MIMO) radar. The propagator method (PM) is extended to jointly estimate the direction of departure (DOD), the direction of arrival (DOA) and the polarization parameters. The PM avoids the singular value decomposition (SVD) of the covariance matrix of the received signals so that the computational complexity is reduced. In addition, the closely spaced targets can be well distinguished by polarization diversity. The Cramer-Rao bounds (CRBs) of the estimated parameters are derived. The position of a target is calculated based on the estimated angles. The simulation results demonstrate that the proposed approach can achieve better performance compared with conventional methods of target localization.